2013
DOI: 10.1016/j.exger.2012.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Establishing cellular stress response profiles as biomarkers of homeodynamics, health and hormesis

Abstract: Aging is the progressive shrinkage of the homeodynamic space. A crucial component of the homeodynamic space is the stress response (SR), by virtue of which a living system senses disturbance and initiates a series of events for maintenance, repair, adaptation, remodeling and survival. Here we discuss the main intracellular SR pathways in human cells, and argue for the need to define and establish the immediate and delayed stress response profiles (SRP) during aging. Such SRP are required to be established at s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
71
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(74 citation statements)
references
References 57 publications
3
71
0
Order By: Relevance
“…However, a progressive accumulation of molecular damage and its effects on the interacting molecular networks leads to the reduction in the functional homeodynamic space, and effectively increases the vulnerability zone, thus allowing for the occurrence and emergence of age-related diseases. Alzheimer's disease, cancer, cataracts, type 2 diabetes, osteoporosis, Parkinson's disease, sarcopenia, and other age-related diseases are the result of reduced homeodynamic space of the individual (Demirovic and Rattan, 2013). Thus, a progressive shrinkage of the homeodynamic space is the hallmark of aging and the cause of origin of all age-related diseases.…”
Section: Homeostasis Versus Homeodynamicsmentioning
confidence: 98%
See 1 more Smart Citation
“…However, a progressive accumulation of molecular damage and its effects on the interacting molecular networks leads to the reduction in the functional homeodynamic space, and effectively increases the vulnerability zone, thus allowing for the occurrence and emergence of age-related diseases. Alzheimer's disease, cancer, cataracts, type 2 diabetes, osteoporosis, Parkinson's disease, sarcopenia, and other age-related diseases are the result of reduced homeodynamic space of the individual (Demirovic and Rattan, 2013). Thus, a progressive shrinkage of the homeodynamic space is the hallmark of aging and the cause of origin of all age-related diseases.…”
Section: Homeostasis Versus Homeodynamicsmentioning
confidence: 98%
“…In a normal, healthy, and young individual, the complex network of stress responses, damage control, and continuous remodeling constitute a functional homeodynamic space (Demirovic and Rattan, 2013). Since no biological system can be 100% perfect 100% of the time, there is a probability of imperfect homeodynamics giving rise to a zone of vulnerability, manifested in ageindependent diseases and mortality.…”
Section: Homeostasis Versus Homeodynamicsmentioning
confidence: 99%
“…Moreover, human herpes virus 4 or EBV encodes RNAs that can be transferred from infected to uninfected cells by EVs [114][115][116]. The uptake of EVs from EBV-infected cells by epithelial cells results in activation of growth-stimulating signaling pathways and can manipulate the growth characteristics of neighboring cells [117,118].…”
Section: Extracellular Vesicles and Virusesmentioning
confidence: 99%
“…The expression of significant stress responsiveness of HSPA1A is often regarded as a potential biomarker to evaluate oxidative cytotoxicity (Demirovic and Rattan 2012;Xin et al 2012). A recent study has shown that stable metabolically competent HepG2 cells containing a human HSPA1A promoter-driven luciferase reporter (HepG2-luciferase cells) could be used for assessing the toxicity of organic pollutants present in air (Xin et al 2012).…”
Section: Introductionmentioning
confidence: 99%